Role of E-Commerce in Indian Banking Industry: Issues And Concern - Shekhar, Shashank (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
E-commerce stands for electronic commerce. E-commerce is improving standard among the business community in worlds, about the opportunities offered by E-commerce. E-commerce as part of the information technology revolution became widely used in the world trade in general and Indian economy in particular. With advancements in technology, there have been many changes has been occupied. Indian banks have been playing an essential role with the e-commerce. Present scenario Banks are facing many issues and challenges by the e-commerce. In the backdrop of all these developments the present paper makes an attempt to: highlight the challenges of e-commerce in Indian banks, and to understand the issues of e-commerce in Indian banks. The paper also highlights the challenges faced by Indian banks in adoption of technology and recommendations are made to tackle these challenges. The paper concludes that in years to come e- banking will not be acceptable mode of banking but preferred mode of banking. KEYWORDS:Electronic Commerce, Challenges, Business, E-Banking, Issues, Economy, Information Technology.